EFL Learners’ Perceptions on Wordwall Implementation in Learning Vocabulary - Anggraini, Rishma; Megawati, Fika; Agustina, Sheila; Thongbab, Sanitpim; Asmara, Candra Hadi (Universitas PGRI Adi Buana Surabaya, 2025)
Vocabulary mastery plays a very important role in the ability to communicate in spoken dan written English skills. Effective vocabulary learning can improve students’ language skills, allowing them to use foreign languages with greater confidence and fluency in a variety of communication situations. However, in English language learning, students often experience difficulties in remembering and memorizing vocabulary. Therefore, it is important to integrate technology and interactive learning media in the English learning process. This approach is expected to provide a more flexible, effective, and enjoyable experience for students. This study aims to find out how students perceive the use of Wordwall in learning English vocabulary. The study involved 15 grade 4 and 5 students from Ban Loei Wangsai School, Thailand. By using a qualitative approach and interview as the main instrument, this research was conducted. The interview results showed that the students feel that learning using Wordwall is fun and helps them remember vocabulary more easily. Wordwall also proved to be able to increase their motivation and interest in learning English. These findings provide a clear picture of the effectiveness of Wordwall in supporting English language learning, especially in terms of vocabulary acquisition, and encourage the use of interactive media in the primary school context. This study implies that English teachers need to be creative in their classroom instruction including giving variation in the learning through the implementation of digital application